Exploring the Gender Gap in Teleworking from Home. The Roles of Worker's Characteristics, Occupational Positions and Gender Equality in Europe - Stefanie Kley; Thordis Reimer (Social Indicators Research, 2023)
Previous research suggests an under-representation of women among teleworkers before the Covid-19 pandemic. However, we know little about whether such a gender gap was substantial, and whether it could be explained by occupational gender segregation. We explore whether a gender gap in regularly teleworking existed in the EU-28 and analyse its possible constituents, drawing on data from the European Working Conditions Survey 2015. To form a group of potential teleworkers, the analytical sample was restricted to employees who made use of information and communication technology (N0.167em≈0.167em16,000). Country fixed effects regression and multilevel models were applied. The results show that women were under-represented among teleworkers compared to men, also when occupational gender segregation is taken into account; the remaining gender gap in telework is estimated at 10%. For women, working part-time and working in the private sector was associated with lower incidences of telework, but not for men. Country characteristics explain a small but significant share of telework incidence. In countries that rank high on the Gender Equality Index and have a large public sector, telework was widespread, whereas it was less present in countries with higher shares of women in the fields of science and engineering. The findings support the view that the gender gap in teleworking from home is a matter of historically grown gender inequality.
Keywords: 300; Gender equity; Telecommute; Gender gap; Occupational gender segregation; Multilevel analyses; Europe